Public-Private Collaboration on Productive Development in Chile - Andrés Zahler; Claudio Cristian Bravo Ortega; Daniel Goya; José Miguel Benavente H. (Inter-American Development Bank (IDB), 2014)
This Working Paper provides an in-depth analysis of public-private collaboration (PPC) in Chilean productive development policies (PDPs) through five case studies under two specific polices: the Technology Consortia Program and the National Cluster Policy. The analysis is based on a set of more than 30 semi-structured, in-depth interviews, and is complemented by official written information on the workings of each of the instruments and particular cases. The most significant conclusion that emerges is the importance of having institutions that allow the government to learn from the implementation of new policies in order to improve them over time.
hdl:11319/6481
Keywords: O43; D71; D78; L52; 330; Public-private collaboration; Productive development; Chile